Efficient capture of CO2 from flue gas at high temperature by tunable polyamine‐based hybrid ionic liquids. Issue 1 (12th September 2019) - Shi, Guiling; Zhao, Hongqin; Chen, Kaihong; Lin, Wenjun; Li, Haoran; Wang, Congmin
Abstract: For an ideal absorbent for CO2 capture from flue gas, there are some key features including easy preparation, high stability, low absorption enthalpy, high capacity at high temperature and excellent reversibility. Herein, several polyamine‐functionalized ionic liquids (ILs) were easily prepared from cheap polyamines and lithium salts, which exhibited significantly improved stability due to the presence of multisite coordinating interactions. The viscosity was reduced by introducing polyalcohol‐based ILs, leading to polyamine‐based hybrid ILs. Interestingly, these polyamine‐based hybrid ILs exhibited high CO2 capacity (4.09 mmol/g, 0.1 bar) at high temperature (80°C) and excellent reversibility in the presence of H2 O and O2, which is superior to many other good absorbents. Moreover, these ILs also showed good performance for CO2 capture from stimulated air (2.10 mmol/g, 380 ppm). We believe that this method with easy preparation, low cost, high efficiency and excellent reversibility has a great potential in the industrial capture of CO2 from flue gas.